An Optimized Adsorbent Sampling Combined to Thermal Desorption GC-MS Method for Trimethylsilanol in Industrial Environments - Jae Hwan Lee; Chunrong Jia; Yong Doo Kim; Hong Hyun Kim; Tien Thang Pham; Young Seok Choi; Young Un Seo; Ike Woo Lee (International Journal of Analytical Chemistry)
Trimethylsilanol (TMSOH) can cause damage to surfaces of scanner lenses in the semiconductor industry, and there is a critical need to measure and control airborne TMSOH concentrations. This study develops a thermal desorption (TD)-gas chromatography (GC)-mass spectrometry (MS) method for measuring trace-level TMSOH in occupational indoor air. Laboratory method optimization obtained best performance when using dual-bed tube configuration (100 mg of Tenax TA followed by 100 mg of Carboxen 569), n-decane as a solvent, and a TD temperature of 300°C. The optimized method demonstrated high recovery (87%), satisfactory precision (<15% for spiked amounts exceeding 1 ng), good linearity (R2=0.9999), a wide dynamic mass range (up to 500 ng), low method detection limit (2.8 ng m−3 for a 20-L sample), and negligible losses for 3-4-day storage. The field study showed performance comparable to that in laboratory and yielded first measurements of TMSOH, ranging from 1.02 to 27.30 μg/m3, in the semiconductor industry. We suggested future development of real-time monitoring techniques for TMSOH and other siloxanes for better maintenance and control of scanner lens in semiconductor wafer manufacturing.